Loss of function of VdDrs2, a P4-ATPase, impairs the toxin secretion and microsclerotia formation, and decreases the pathogenicity of Verticillium dahliae - Ren, Hui; Li, Xianbi; Li, Yujie; Li, Mengjun; Sun, Jiyuan; Wang, Fanlong; Zeng, Jianyan; Chen, Yang; Wang, Lei; Yan, Xingying; Fan, Yanhua; Jin, Dan; et al. (Frontiers in Plant Science, 2022)
Four P4-ATPase flippase genes, VdDrs2, VdNeo1, VdP4-4 and VdDnf1 were identified in Verticillium dahliae, one of the most devastating phytopathogenic fungi in the world. Knock out of VdDrs2, VdNeo1 and VdP4-4, or knock down of VdDnf1 significantly decreased the pathogenicity of the mutants in cotton. Among the mutants, the greatest decrease in pathogenicity was observed in ΔVdDrs2. VdDrs2 was localized to plasma membrane, vacuoles and TGN. In vivo observation showed that the infection of the cotton by ΔVdDrs2 was significantly delayed. The amount of two known Verticillium toxins, sulfacetamide and fumonisin B1 in the fermentation broth produced by the ΔVdDrs2 strain was significantly reduced, and the toxicity of the crude Verticillium wilt toxins to cotton cells was attenuated. In addition, the defect of VdDrs2 impaired the synthesis of melanin and the formation of microsclerotia, and decreased the sporulation of V. dahliae. Our data indicate a key role of P4 ATPases-associated vesicle transport in toxin secretion of disease fungi and support the importance of mycotoxins in the pathogenicity of V. dahliae.